The main needs of cosplay players with different participation in the game - Ksionda, Olga G. (Journal of the Belarusian State University. Philosophy and Psychology, 2019)
The concept of cosplay is being defined as a game activity, the motivation and needs of its players are discussed. The leading needs of cosplayers, which form the basis of the motivation for their participation in the game, described in the study (using an essay analysis method) are described. Cosplay players with different experience choose it based on their basic needs: communication, recognition of their own importance and success, pleasure. The data obtained will allow to adjust the program of assistance to adolescents and young men with problems in communication and having game dependencies.
Keywords: cosplay; game activity; cosplay players; subculture; needs of cosplay players